Surface plasmon coupling effects on the förster resonance energy transfer from quantum dot into rhodamine 6G. (30th April 2021) - Chen, Chien-Yu; Ni, Chia-Chun; Wu, Ruei-Nan; Kuo, Sheng-Yang; Li, Chia-Hao; Kiang, Yean-Woei; Yang, C C
Abstract: Rhodamine 6G (R6G) molecules linked CdZnSeS/ZnS green-emitting quantum dots (QDs) are self-assembled onto Ag nanoparticles (NPs) for studying the surface plasmon (SP) coupling effect on the Förster resonance energy transfer (FRET) process from QD into R6G. SP coupling can enhance the emission efficiency of QD such that FRET has to compete with QD emission for transferring energy into R6G. It is found that FRET efficiency is reduced under the SP coupling condition. Although R6G emission efficiency can also be enhanced through SP coupling when it is directly linked onto Ag NP, the enhancement decreases when R6G is linked onto QD and then the QD-R6G complex is self-assembled onto Ag NP. In particular, R6G emission efficiency can be reduced through SP coupling when the number of R6G molecules linked onto a QD is high. A rate-equation model is built for resembling the measured photoluminescence decay profiles and providing us with more detailed explanations for the observed FRET and SP coupling behaviors.